Implementasi Teori Belajar Berdasarkan Aliran Psikologi Humanistik pada Pembelajaran IPAS Kelas V SD Negeri 050728 Tanjung Pura - Fahrunnisa Fahrunnisa; Violla Fathna Fisa (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
In science and science learning, the emphasis is on concepts related to people's lives and the environment. Students are expected to have basic abilities for logical and critical thinking, curiosity, inquiry, problem solving, and skills in social life. The humanistic learning model views students as subjects who are free to determine the direction of their lives. Students are directed to be fully responsible for their own lives and also for the lives of others. In this research, researchers used a qualitative research approach. Several approaches that are worth using in this method are dialogical, reflective and expressive approaches. The dialogical approach invites students to think together critically and creatively. The teacher does not act as a teacher who only provides material intake that students need as a whole, but the teacher only acts as a facilitator and dialogue partner. The population in this research is all teachers and students. Meanwhile, the samples taken in this research were school principals, science and science teachers and students. Humanistic education in science and science learning is an alternative in realizing education that has a very significant influence on future generations. Applying humanistic education in learning can increase students' intrinsic motivation. So that students tend to be enthusiastic and involve themselves actively in learning when they are listened to, appreciated, cared for and treated well. Applying humanistic education to the science and science learning process grade V at SD Negeri 050728 Tanjung Pura can be done using procedures such as planning, implementation and evaluation.